New Organizational Culture on Work Motivation and Employee Performance Post-Merger - Kurniawati, Kurniawati (widya balina, 2023)
This study aims to what extent the role of the new organizational culture that was implemented could increase work motivation and employee performance after the merger that occurred at Bank Syariah Indonesia Renon Denpasar Bali branch office. This study found that organizational culture has a relationship with an increase or decrease in work motivation and employee performance. it can be seen that at the time of the merger there was a decrease in the target achieved, but after the socialization process began there was an increase in the target achieved. This study uses descriptive qualitative research, with data collection techniques through observation, interviews, and documentation. Data analysis uses the Miles and Huberman models, with data analysis techniques using data reduction, data display, and verification. The results of the study show that the new culture applied to Bank Syariah Indonesia is able to increase work motivation and employee performance. This is due to the effectiveness of implementing a new performance-based organizational culture. Performance-based organizational culture directs employees to focus on achieving company goals through predetermined targets.